A Review of Caffeine Adsorption Studies onto Various Types of Adsorbents - Javier Andrés Quintero-Jaramillo; Javier Ignacio Carrero-Mantilla; Nancy Rocío Sanabria-González (The Scientific World Journal)
A systematic literature review of publications from 2000 to 2020 was carried out to identify research trends on adsorbent materials for the removal of caffeine from aqueous solutions. Publications were retrieved from three databases (Scopus, Web of Science, and Google Scholar). Words “adsorption AND caffeine” were examined into titles, abstracts, and keywords. A brief bibliometric analysis was performed with emphasis on the type of publication and of most cited articles. Materials for the removal of caffeine were classified according to the type of material into three main groups: organic, inorganic, and composites, each of them subdivided into different subgroups consistent with their origin or production. Tables resume for each subgroup of adsorbents the key information: specific surface area, dose, pH, maximum adsorption capacity, and isotherm models for the removal of caffeine. The highest adsorption capacities were achieved by organic adsorbents, specifically those with granular activated carbon (1961.3 mg/g) and grape stalk activated carbon (916.7 mg/g). Phenyl-phosphate-based porous organic polymer (301 mg/g), natural sandy loam sediment (221.2 mg/g), composites of MCM-48 encapsulated graphene oxide (153.8 mg/g), and organically modified clay (143.7 mg/g) showed adsorption capacities lower than those of activated carbons. In some activated carbons, a relation between the specific surface area (SSA) and the maximum adsorption capacity (Qmax) was found.